FENOMENA PEREMPUAN PEROKOK DI PEKANBARU - Rizkina Putri R; Evawani Elysa Lubis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Advances in technology led to lifestyles also change, one of the lifestyle of smoking among women in big cities. It also affects lifestyle in major city where the lifestyle of smoking among women in Pekanbaru began implicated. Views of women smokers in Singapore can be found in public places such as cafes, coffee shop, even a campus environment. Smoking is dangerous behavior, especially for women, in which smoking can cause infertile, fetal damage, infertility, and physical changes are visible. In addition, women smokers are also assessed negatively by the public as being labeled as a hussy. This study aims to determine the motive Because in order to motive and female smokers, female smokers communications experience in Pekanbaru, and the significance of smoking for women smokers in Pekanbaru.This study uses qualitative research methods to conduct phenomenological approach. Subjects in this study consisted of six people. Data collection techniques are grouped into three sections, namely; in-depth interviews, observation, and documentation. This study uses data analysis interactive model of Miles and Hubermen, using a technique that checks the validity of the data through the extension of participation and triangulation.These results indicate that Because motive female smokers in Singapore namely the kengininan from within myself to smoke because often see women smokers, have the parents are smokers, friends seperkumpulan are also smokers, never offered a cigarette samples free diacara music festivals, and has its own views on female smokers. In order to motive while woman smokers in Pekanbaru are to get solidity feelings with the group, showed identity, gain a sense of calm, and let go of the desire to smoke. During his life as smokers, woman smokers in Pekanbaru get a pleasant communication experience that is more easily accepted by the group and individuals, preferably, bolder, more confident and able to free themselves. Through life experiences as women smokers, those smoking interpret as a friend, smoking as an outlet from life's problems, and smoking is a must.Keyword : Phenomenon, Women, Smokers.